Serum Apoprotein (ApoA1 and ApoB) in Myocardial infarction - Jhuma, Khadija Akther; Hoque, MM (Journal of Bangladesh College of Physicians and Surgeons, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> 30 diagnosed cases (Male26, Female 4) of MI (myocardial infarction) with the mean age of 55.5±9.8 years (range 40- 70 years) were included in a case control study to evaluate their apoprotein status. Serum apoA1 and apoB were measured and compared with those of age and sex matched healthy control subjects. Mean serum apoA1 concentration found significantly low in MI cases (91.84± 11.2 mg/dl) compared to control ( 123.2±10.5 mg/dl) and that of apoB found significantly high in MI cases( 135.3± 23.0 mg/dl ) compared to control (66.2±10.0 mg/dl).Serum apoB/apoA1 ratio of MI cases (1.49±0.3) also found significantly higher than that of control (0.54±0.1) .Since the serum apoA1 and apoB concentration stand for relatively more comprehensive measure of antiatherogenic and atherogenic potential respectively rather than the traditional lipid profile ; measurement of this apoprotein and their ratio may be more robust and specific marker for identification of individuals at risk of MI even in individuals with normal traditional lipid profile. Key word: ApoA1, ApoB, MI DOI: 10.3329/jbcps.v26i2.4181 J Bangladesh Coll Phys Surg 2008; 26: 62-66